1996
DOI: 10.1093/genetics/143.3.1321
|View full text |Cite
|
Sign up to set email alerts
|

Scalloped wings Is the Lucilia cuprina Notch Homologue and a Candidate for the Modifier of Fitness and Asymmetry of Diazinon Resistance

Abstract: The Scalloped wings (Scl) gene of the Australian sheep blowfly, Lucilia cuprina, is shown to be the homologue of the Drosophila melanogaster Notch gene by comparison at the DNA sequence and genetic levels. A L. cuprina genomic fragment, which shows strong identity with the Notch (N) gene at the molecular level, hybridizes to the location of the Scl gene on polytene chromosomes. The two genes are functionally homologous; the dominant and recessive Notch-like phenotypes produced by mutations in the Scl gene allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…In this case, the modifier (which rescued delayed development associated with resistance) was identified because it was on a different linkage group, 63 and because a difference in the fitness of field‐collected resistant strains was noticed over a period of approximately 10 years. It was subsequently reported that resistance to diazinon was conferred by mutations of the carboxylesterase E3, 64 and proposed that Scalloped wings was the fitness modifier 64 . It has been proposed that duplication of ace‐1 in C. pipiens and A. gambiae is another example of a modifier locus (keeping together one copy of the susceptible allele with a copy of the resistant allele to compensate for the poor enzyme activity of the resistant copy against acetylcholine), 65,66 but separating the resistance allele and the modifier for experimental tests of fitness is in that case much more difficult 53 .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the modifier (which rescued delayed development associated with resistance) was identified because it was on a different linkage group, 63 and because a difference in the fitness of field‐collected resistant strains was noticed over a period of approximately 10 years. It was subsequently reported that resistance to diazinon was conferred by mutations of the carboxylesterase E3, 64 and proposed that Scalloped wings was the fitness modifier 64 . It has been proposed that duplication of ace‐1 in C. pipiens and A. gambiae is another example of a modifier locus (keeping together one copy of the susceptible allele with a copy of the resistant allele to compensate for the poor enzyme activity of the resistant copy against acetylcholine), 65,66 but separating the resistance allele and the modifier for experimental tests of fitness is in that case much more difficult 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, QTL mapping has been successfully applied in mice where QTLs affecting fluctuating asymmetry in skull morphology have been identified (Leamy et al 1998). Similarly, recombination mapping protocols have been used to identify Notch as a candidate gene responsible for the reduction of fluctuating asymmetry in blowflies (Davies et al 1996).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…A well-understood example concerns diazinon insecticide resistance in blowflies, Lucilia cuprina (e.g., Clarke and McKenzie 1987;Davies et al 1996;overview by Clarke 1997). Resistance to diazinon is essentially conferred by the Rop-1 locus and is correlated with increased levels of fluctuating asymmetry in several bristle traits.…”
Section: Epistasismentioning
confidence: 99%
See 1 more Smart Citation
“…Its developmental origin, however, is mostly unclear. There is only one case in which speci¢c genes with a major in£uence on nondirectional asymmetry have been identi¢ed (Davies et al 1996;Batterham et al 1996), and another study reported a number of quantitative trait loci (Leamy et al 1997). But even in these examples, the role of these genes in the development of asymmetry is not fully understood.…”
Section: Introductionmentioning
confidence: 99%